2014
DOI: 10.1111/padm.12106
|View full text |Cite
|
Sign up to set email alerts
|

Public Administration and the Integrity of the Electoral Process in British Elections

Abstract: Although Britain has often been held up as being a model of electoral integrity, recent controversies have suggested that this perception may not be wholly justified. This article explores overall standards of electoral administration across Britain, utilizing performance reporting data for returning officers in the 2010 general election to outline a comprehensive measure for the integrity of the administration of the electoral process. Discussion begins by outlining the question of electoral integrity and, mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 31 publications
1
27
0
Order By: Relevance
“…This emphasises that elections are like other public services, such as schools and hospitals, which have differing levels of performance and efficiency. The effects of policy tools, management structures and the use of resources amongst electoral management bodies should therefore be investigated (Alvarez, Atkeson, andHall 2012a, 2012b;Clark 2015Clark , 2016James 2014aJames , 2014bMontjoy 2008).…”
Section: Existing Research On Funding Electoral Servicesmentioning
confidence: 99%
See 2 more Smart Citations
“…This emphasises that elections are like other public services, such as schools and hospitals, which have differing levels of performance and efficiency. The effects of policy tools, management structures and the use of resources amongst electoral management bodies should therefore be investigated (Alvarez, Atkeson, andHall 2012a, 2012b;Clark 2015Clark , 2016James 2014aJames , 2014bMontjoy 2008).…”
Section: Existing Research On Funding Electoral Servicesmentioning
confidence: 99%
“…In the UK, information on how much money is spent is not routinely reported, however, the Electoral Commission undertook an earlier financial survey of the cost of running elections after it developed a bespoke accounting method (Electoral Commission 2012a). This enabled Clark (2014Clark ( , 2015Clark ( , 2016 to undertake the first studies that actually used real data on spending. The Electoral Commission has also reported on the costs of the AV referendum (Electoral Commission 2012b) and plans to publish information about the costs of the EU referendum.…”
Section: Existing Research On Funding Electoral Servicesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, when studies then investigated the effects of formal-legal independence using large n, cross-national studies the evidence was mixed (Birch 2008, Norris 2015, Lindberg and van Ham 2015. More recent research has identified the challenges that election officials face delivering elections (James, 2014), the effects of funding (Clark 2014(Clark , 2015 and the effect of policy instruments used within EMBs (Alvarez et al 2012b(Alvarez et al , 2012aGoggin et al 2012;James 2013). Yet there remains a huge lacuna on 'what works?…”
Section: [Insert Table 1 About Here]mentioning
confidence: 99%
“…This involves identifying and assessing the outputs that they produce; the economic efficiency with which they produce them; and, the efficacy of those outputs for the desired outcomes (Table 1). The responsiveness of EMBs to the needs of citizens and their employees are also included into the framework, as are the levels of probity and accountability within the organisations (also see: Bland et al 2012;Clark 2015;Elklit and Reynolds 2002).…”
Section: Electoral Management: the State Of The Fieldmentioning
confidence: 99%